2021
DOI: 10.15252/embr.202152532
|View full text |Cite
|
Sign up to set email alerts
|

Hepsin regulates TGFβ signaling via fibronectin proteolysis

Abstract: Transforming growth factor-beta (TGFb) is a multifunctional cytokine with a well-established role in mammary gland development and both oncogenic and tumor-suppressive functions. The extracellular matrix (ECM) indirectly regulates TGFb activity by acting as a storage compartment of latent-TGFb, but how TGFb is released from the ECM via proteolytic mechanisms remains largely unknown. In this study, we demonstrate that hepsin, a type II transmembrane protease overexpressed in 70% of breast tumors, promotes canon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 84 publications
1
22
0
2
Order By: Relevance
“…After activation of TGF-β signaling, TGF-β-associated ligands bind to corresponding receptors I and II ( de la Cruz-Merino et al, 2009 ) and then transfer extracellular signals to nuclear components through canonical TGF-β pathways, such as the TGF-β/Smad pathway, and noncanonical TGF-β pathways, such as the p38/mitogen-activated protein kinase (MAPK) pathway, GTP pathway, PI3K/AKT pathway, and NF-κB pathway ( Patil et al, 2011 ; Bataller et al, 2019 ; Chang and Pauklin, 2021 ; Choi et al, 2021 ; Hou et al, 2021 ). TGF-β has often been implicated in carcinogenesis, and studies have demonstrated that TGF-β has both oncogenic and tumor-suppressive functions in cancer regulation mechanisms ( Yu and Feng, 2019 ; Belitškin et al, 2021 ). The antitumor ability of TGF-β functions occur through cytostatic and proapoptotic effects ( Ahmadi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…After activation of TGF-β signaling, TGF-β-associated ligands bind to corresponding receptors I and II ( de la Cruz-Merino et al, 2009 ) and then transfer extracellular signals to nuclear components through canonical TGF-β pathways, such as the TGF-β/Smad pathway, and noncanonical TGF-β pathways, such as the p38/mitogen-activated protein kinase (MAPK) pathway, GTP pathway, PI3K/AKT pathway, and NF-κB pathway ( Patil et al, 2011 ; Bataller et al, 2019 ; Chang and Pauklin, 2021 ; Choi et al, 2021 ; Hou et al, 2021 ). TGF-β has often been implicated in carcinogenesis, and studies have demonstrated that TGF-β has both oncogenic and tumor-suppressive functions in cancer regulation mechanisms ( Yu and Feng, 2019 ; Belitškin et al, 2021 ). The antitumor ability of TGF-β functions occur through cytostatic and proapoptotic effects ( Ahmadi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The MCF10A (ATCC Cat# CRL-10317, RRID:CVCL_0598) cell line was obtained from the American Type Culture Collection and cultured as described previously [3] in MCDB 170 (US Biological, Salem, MA, USA) supplemented with 5 lgÁmL À1 insulin, 70 lgÁmL À1 bovine pituitary extract, 0.5 lLÁmL À1 hydrocortisone, 5 ngÁmL À1 EGF, 5 lgÁmL À1 human transferrin, and 0.01 lM isopropretenol (all from Sigma Aldrich, St.Louis, MO, USA). The MCF10A-based cell lines harboring the pLenti6-TGF-b1V5 and inducible hepsin overexpression constructs were published previously [3,8].…”
Section: Cell Linesmentioning
confidence: 99%
“…MCF10A growth experiments were performed in Cultrex RGF Basement Membrane Extract, Type 2 (R&D Systems, 3533-005-02, Minneapolis, MN, USA) 3D matrix and serum-free media as described in [3,8]. Human tumor samples were obtained from elective breast cancer surgeries between May 2019 and May 2020 at the Helsinki University Central Hospital (Ethical permit: 243/13/03/02/2013/TMK02 157 and HUS/ 2697/2019 approved by the Helsinki University Hospital Ethical Committee).…”
Section: D Cell and Pdec Culture Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the kidney, hepsin polymerizes uromodulin to inhibit bacterial infection in the urinary tract [17][18][19]. In breast cancers, hepsin cleaves fibronectin in the extracellular matrix to enhance transforming growth factor-beta signalling and cancer progression [20,21]. In the inner ear, hepsin is essential for auditory nerve function [22,23].…”
Section: Introductionmentioning
confidence: 99%